KEBIJAKAN MONETER, SEKTOR PERBANKAN, DAN PERAN BADAN SUPERVISI - Ahmad Erani Yustika; Eka Heni Sulistiani (University of Merdeka Malang, 2010)
Besides fiscal policy, monetary policy was the main instrument in designing economic policy. of course, therole of central bank, in this case Bank Indonesia, was so vital in formulating monetary policy. Since someyears ago, Bank Indonesia had decided that the target of monetary policy was only to keep inflation, knowninflation targeting. This policy had a strong point because BI could focus in keeping economic stability.However, the weakness of this policy was its tendency not to be adaptive with national economic situation,such as poverty and unemployment problems. Anyway, BI independence also gave a good benefit because BIcould formulate a policy as needed without any intervention from other interest, like politic. However, in theimplementation, the independence should not come into management, including monetary policy management.This was the important thing in giving a chance for BSBI (Supervision Board of Bank Indonesia) towatch BI, including monetary policy, without disturbing BI independence in formulating a policy. Thus, thepurpose of independence still became a domain owned by BI, but the implementation of the policy could bethe object of watching.